Nonlinear broadband piezo-magneto-elastic energy harvester in bistable and monostable configurations - Krishnasamy, M. (2019)
Based on recent research investigations, the narrow bandwidth of vibration based linear energy harvester can be magnified into wide bandwidth using nonlinear effect on bending stiffness of the cantilevered energy harvesters. In this paper, we simulate the analytical models to explain the nonlinear behavior of broadband piezo-magneto-elastic energy harvester in bistable and monostable configurations. By varying distance between the two magnets in order to acquire attractive as well as repulsive magnetic forces for the investigation of the tuned resonant frequency, total stiffness of cantilever along with electrical response. Sustainable large electrical response is observed for wide frequency range achieving broadband frequency energy harvester.